The Emerald Handbook of Research Management and Administration Around the World - Kerridge, Simon; Poli, Susi; Yang-Yoshihara, Mariko (Emerald Publishing, 2024)
The ebook edition of this title is Open Access and freely available to read online. Over past decades, scholars and practitioners around the world observed an emergence of professionals, research managers and administrators (RMAs) who play an essential role in the advancement of academic research. RMAs have extensive knowledge of the research ecosystem, including funding opportunities, proposals, budgeting and pricing, ethics, open research, project management, finance, negotiation, strategy, systems, and assessment. Until now, limited efforts have been made to investigate RMAs in a cross-regional, comparative manner, or to understand the recent surge of the profession in a larger policy context. Addressing this gap, an international group of experts share diverse perspectives to provide a comprehensive account of RMA as a profession, offer an analytical framework to understand their role in higher education and academic science. Covering countries in Africa, Australasia, East Asia and India, Western Europe, Central and Eastern Europe, the Middle East, North America, and South America, the work provides trans-cultural coverage of the profession. Drawing on theories from related fields, it also provides insights and understanding of RMAs as a social phenomenon. The Emerald Handbook of Research Management and Administration Around the World is the most comprehensive book about practitioners working in research management and administration. The book provides basic knowledge for students and professionals considering a career in this field, and serves as reference material for policymakers as well as academic researchers. By presenting evidence-based observations from around the world and discussing global trends, this text promotes social awareness of RMAs, shares state-of-the-art knowledge on the profession, and offers insights into the future of academic research.